Bondi to the Baltic - McCombe, John (Wild Dingo Press, 2020)
Take a couple of vintage cars and their owners' determination to drive them on a pilgrimage from Australia to Finland and you have a fascinating story told through photos and the distillation of blogs and diary entries by some foolhardy, adventurous blokes. Starting out from Thailand, their travels took them through Laos, China, Kyrgyzstan, Kazakhstan, Uzbekistan, Turkmenistan, Azerbaijan, Georgia, Armenia, Russia and Finland - a six-month journey spread over two legs in successive years. Told in an engaging, self-deprecating and personal style, the reader enters the journey, every step of the way: following the ancient Silk Road route into the mountains of south-west and western China and the Tibetan Plateau where Muslim and Buddhist communities have lived for centuries, through the '-stans', and beyond. Many an adventure, impossibly sticky situations, near misses and regular mechanical breakdowns were inevitably resolved with the support and civility towards this motley group of travellers in their ancient cars, by locals renowned for their hospitality. Nothing was ever too much trouble. They had no sponsor, no professional photographer or filmmaker, no journalist to publish the story, no 'name' to add fame and celebrity, no contract in the pocket for a coffee table book with quality photos and deep, or informed historical and cultural insights, and no travelling mechanical workshop. There was just a determination to get each of these old cars to Helsinki in one piece and smell the roses along the way.